War Machines and Orthodoxy: Unmanned Combat Vehicles and Autonomous Weapons Systems in Eastern Christian-Orthodox Understanding of War - Stanar, Dragan (Journal for the study of religions and ideologies, 2022)
In this paper, the author aims to explain why the use of modern war machines, namely Unmanned Combat Vehicles (UCV) and Autonomous Weapons Systems (AWS), cannot be justified in Eastern Christian-Orthodox ethics of war. The author explains how the moral dimension of war in Eastern Christian Orthodoxy is derived from its ontological nature, which prevents the creation of a just war theory. War is understood as a divine punishment for nations which "fall from God" and it does not have a Manichean nature in which one side represents the Good and the other Evil, unlike Western Christianity which developed not only a Just War Theory but also the concept of a Holy War. Eastern Christian-Orthodoxy perceives war as a combination of a cataclysm and temptation for all involved, creating a morally-tragic situation for all soldiers who are faced with impossible choices. Due to the key implications of the introduction of modern war machines into warfare, namely the elimination of risk and even the elimination of the human element from the process of killing, such machines transform war into a punitive action of the "just" side, a phenomenon more resembling hunting, police enforcement, or even pest control in which the outcome is not in God’s hands but is actually predetermined. The author therefore concludes that modern war machines are fundamentally incompatible with Eastern Christian-Orthodox ethics.